METHODS OF IDENTIFICATION OF MUSCLE TISSUE IN MEAT PRODUCTS. PREREQUISITES FOR CREATING A MULTI–LEVEL CONTROL SYSTEM - Irina M. Chernukha; Natal’ya L. Vostrikova; Daniil V. Khvostov; Elena A. Zvereva; Nadezhda A. Taranova; Anatoly V. Zherdev (Теория и практика переработки мяса)
Unfair production and products that do not comply with the declared labeling are currently an acute problem in the field of technical regulation, including with regard to food safety and quality. Given the high added value and multicomponent composition, finished meat products are among the most susceptible to adulteration. Despite the best efforts of regulatory agencies to counteract these inconsistencies, the hidden substitution of cheaper or lower-grade meats is still widespread. One of the main tasks facing research laboratories and testing centers today is the detection of falsification of food products, as well as standardization and certification of techniques necessary to solve such problems. The manufacturer, aware of the current control methods, can go to the deception, using vegetable protein, new unregistered feed additives. To determine the complex changes that occur in products, it is necessary to use methodological approaches in which it is possible to reliably determine these changes. The paper presents an overview of the most commonly used methodologies for assessing the component composition of meat products. Quality assessment of meat products includes control of components of finished products. The most difficult task is to determine the proportion of muscle protein in multicomponent meat products that have undergone heat treatment.